ANALISIS PENGUMPULAN PIUTANG PADA CV. CAHAYA INTI ABADI SAMARINDA - Rusvianty, Vivi (EKONOMIA, 2013)
VIVI RUSVIANTY, 'Analysis of Collecting Receivables at CV. Samarinda Eternal Light Core ". Under the guidance of Mr. Robin Jonathan as a mentor I and Mrs. Elfreda A. Lau as mentors II.Based on the overall results of the study can be addressed by looking at the results of analysis of the accounts receivable turnover rate in the first period by 8 and 7 in the second period, the collection of the receivable exceeds the company's policy is for 14 days for 45 days and during the subsequent period of 51 days which means that the level of accounts receivable turnover , collection of the receivable is not good enough.So based on the results of the analysis it can be concluded that the policy - a policy the company's trade receivables turnover is not optimal for uncollectible accounts receivable due. Then the hypothesis is rejected because the accounts receivable turnover decreased in 2012 compared to 2011.